2021
DOI: 10.1002/ejic.202100567
|View full text |Cite
|
Sign up to set email alerts
|

Two Lead‐Free Organic‐Inorganic Hybrid Halides: Exploring Dielectric Switching and Photoluminescence Integrated in Crystals

Abstract: Organic‐inorganic hybrid halides have attracted widespread attention in optics, electricity, magnetism. In particular, some of them can have a combination of luminescence and switching characteristics, providing a potential for a single device unit to meet multiple application requirements. Herein, we reported two novel organic‐inorganic hybrid single‐crystals (CTA)2ZnCl4 (1; CTA=3‐chloro‐2‐hydroxypropyltrimethylammonium) and (CTA)2[InCl5(H2O)] ⋅ H2O (2), exhibiting long lifetime blue emission upon UV excitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Among these, the polyhedron with indium as central ions and halogen and water molecules as ligands [In X m (H 2 O) n , X = halogen anions, m + n = 6] are well known and have been extensively studied. The coordination number of indium can vary from four to seven by altering bond lengths of ligands. This is in particular true when indium is coordinated with halogen anions and oxygen in water molecules, among which the latter bond is relatively weak. This allows the whole framework to not collapse if the water molecules are ionized (loss of protons) or even removed.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, the polyhedron with indium as central ions and halogen and water molecules as ligands [In X m (H 2 O) n , X = halogen anions, m + n = 6] are well known and have been extensively studied. The coordination number of indium can vary from four to seven by altering bond lengths of ligands. This is in particular true when indium is coordinated with halogen anions and oxygen in water molecules, among which the latter bond is relatively weak. This allows the whole framework to not collapse if the water molecules are ionized (loss of protons) or even removed.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is found that the In­(III) atom and different kinds of halogens can form diverse indium halide anions, which can combine with organic ammonium to generate inorganic–organic hybrid compounds A n –3 [In III X n ] (A = organic ammonium cation) with various structures and different compositions. Jakubas et al. obtained two alkylammonium halogenoindium­(III) phase transition materials, [(C 2 H 5 ) 4 N]­InBr 4 and [(CH 3 ) 4 N]­InBr 4 , with T p values of 225 and 186 K, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25][26][27][28][29][30][31][32][33] Recently, zinc halides hybrids with stable oxidation states have attracted some attention due to their unique photophysical properties. [34][35][36][37] It is worth noting that replacing toxic Pb 2+ with "green" Zn 2+ significantly reduces the harm to the environment and humans. [38][39][40] For example, based on the compositional engineering strategy, Zhou and co-workers prepared several zinc metal halide: A 2 ZnX 4 (A = Rb, Cs; X = Cl, Br) with or without Cu-doping and their mixed-halide counterparts (Cs 2 ZnCl x Br 4-x :Cu, x = 0−4), blue emitting Cs 2 ZnBr 4 :Cu with a high photoluminescent quantum yield (PLQY) of 57%.…”
Section: Introductionmentioning
confidence: 99%